2021
DOI: 10.1128/mbio.00530-21
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Succinyl Coenzyme A Perturbs the Methicillin-Resistant Staphylococcus aureus (MRSA) Succinylome and Is Associated with Increased Susceptibility to Beta-Lactam Antibiotics

Abstract: mecA -dependent methicillin resistance in MRSA is subject to regulation by numerous accessory factors involved in cell wall biosynthesis, nucleotide signaling, and central metabolism. Here, we report that mutations in the TCA cycle gene, sucC , increased susceptibility to β-lactam antibiotics and was accompanied by significant accumulation of succinyl-CoA, which in turn perturbed lysine succinylation in the proteome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 78 publications
3
12
1
1
Order By: Relevance
“…A total of 3,260 succinylation sites in 799 proteins and 7,935 Kac sites from 1,710 proteins were detected in XN108-WT strain. The numbers of Ksucc and Kac sites reported in this study were greater than those identified previously ( 27 , 28 ), partially because of the benefit of the development and improvement of detection methodology. Another reason might be that different S. aureus strains with different backgrounds were used.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…A total of 3,260 succinylation sites in 799 proteins and 7,935 Kac sites from 1,710 proteins were detected in XN108-WT strain. The numbers of Ksucc and Kac sites reported in this study were greater than those identified previously ( 27 , 28 ), partially because of the benefit of the development and improvement of detection methodology. Another reason might be that different S. aureus strains with different backgrounds were used.…”
Section: Discussioncontrasting
confidence: 61%
“…Nevertheless, the work of PTM identification was seldom carried out in S. aureus . Only Zhang et al ( 27 ) and Campbell et al ( 28 ) detected the protein acetylation and succinylation in S. aureus before. In the present study, we conducted systematic analyses of both Ksucc and Kac modifications in S. aureus XN108, the first ST239 vancomycin-intermediate S. aureus (VISA) strain isolated in China ( 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…9 A previous study has found that succinylation regulates autolysis and β-lactam susceptibility in methicillinresistant S. aureus, suggesting that the modulation of succinylation may affect antimicrobial susceptibility. 10 Our study also found succinylated protein and penicillinbinding protein 2, which may influence the antibiotic binding (Figure 1B). Thus, the drugs that modulate acetylation or succinylation will affect a wide range of functions in S. aureus, including antibiotic susceptibility.…”
Section: F I G U R E 2 Functional Classification and Gene Ontology (G...supporting
confidence: 65%
“…For instance, almost 98% of the mutants of the V. cholerae transposon library present a statistically significant alteration of their PG profile (deviate at least 1SD from the average), and more than the 50% of the mutants presented a variation higher than 2SD of the average of the whole library for at least one muropeptide or a PG-feature) that included loci from all COG categories. These results are in agreement with studies that linked the cell wall with seemingly unrelated pathways/processes (e.g.,(Bancroft et al, 2020; Campbell et al, 2021; Masser et al, 2021)). Conversely, certain mutants in cell wall-annotated genes did not show an altered PG profile suggesting the existence of functional redundancies or condition-specific activities.…”
Section: Discussionmentioning
confidence: 99%